The Influence of Dividend Policy and Company Size on The Company Value - Nurmila, Mila; Jamaludin, Jamaludin; Firstianto, Seno Aji; Sugiyanto, Sugiyanto (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2025)
This study aims to determine the Effect of Dividend Policy and Company Size on the Company Value of PT. Gudang Garam, Tbk Period 2013-2023. This type of research is descriptive quantitative. The population used is the financial statements of PT. Gudang Garam, Tbk Period 2013-2023. Data analysis used includes Dividend Policy (DPR), Company Size (SIZE) and Company Value (PBV), Descriptive test, classical assumption test, hypothesis test, multiple linear regression test, determination coefficient test. This research method uses purposive sampling and the analysis tool used is SPSS 26. The results of the t-test (partial) show that dividend policy has no positive and insignificant effect on company value and company size has a negative and significant effect on company value. The results of the F test (simultaneous) dividend policy and company size have a positive and significant effect on company value.